Pro Apparel: Towards a Leader in Apparel Innovation - Mohamad, Arifha; Md Ramin, Mohd Khairulamiren (Research in Management of Technology and Business, 2022)
Pro Apparel Asia Sdn. Bhd. as a one stop shop for all cycling needs requires additional funding from government agency to expand its business capabilities. While the demand for sports apparel especially for cycling activity increases tremendously, Pro Apparel requires latest machine and technology to be utilised in its production line to increase the products output. A quantitative study conducted through disseminating online survey questions to the people to learn about their attitude towards sports apparel products and determining the elements that influence their purchasing decisions. Based on the results from the online survey, majority of the respondents comes from younger generation who prefer to wear sports apparel in their daily lives without compromising the quality of the apparel that they can purchase in reasonable price. High quality and affordable sports apparel are the attractive factors that lead to the purchasing decision made by the customers. Hence, the additional funding that requested by Pro Apparel can be a major milestone to meet the needs and desire by its customers through fully utilising the current retail technology and innovation.